Use of dietary supplements by physical activity practitioners (Research, Society and Development, 2021)
Introduction: One of the aspects that has defined the consumer society is the growing importance attributed to body image. With this, the search for the practice of physical activities in gyms in its different modalities was consolidated in the various age groups. It is known that the adequate intake of nutrients is related to the improvement of the body's performance in relation to sports performance. In order to maximize results in the exercises, practitioners are led to seek resources in order to achieve the short-term goal. Among these resources, dietary supplements stand out, they can be easily acquired, and are often used improperly for ergogenic and purely aesthetic purposes. Objective: to evaluate, through a review, the prevalence of the use of dietary supplementation by gym users. Method: This is a systematic review about the use of dietary supplements in gym goers conducted at the Medical Literature Analysis and Retrieval Sistem On-line (MEDLINE / PUBMED and Google academic, using the terms: food supplements, physical activity, body image The selection respected inclusion / exclusion criteria previously listed Results: 28 articles were selected, among them 12 met the requirements.The studies show that the prevalence of the use of supplements by gym users is higher in men than in women. reason observed for the use of dietary supplements was the search for muscle hypertrophy, with protein products being the most consumed among the supplements, however, it was observed that the prescription of such supplements is not performed by qualified professionals, being the gym instructors, followed by friends, store sellers, self-prescribing and lastly nutritionists. It was noted that the biggest consumers of dietary supplements are bodybuilders, since it is a modality that mixes muscle development as for better aesthetic results. Conclusion: Therefore, in order to reduce misuse, the presence of a specialized professional is necessary to work in gyms or in places where physical exercise is practiced, providing nutritional guidelines in order to improve the level of information and ensure safe use. of these products.